The Effect of Rural Development on Poverty Gap, Poverty Severity and Local Economic Growth in Indonesia - Handoyo, Felix; Hidayatina, Achsanah; Purwanto, Purwanto (Research and Development Agency Ministry of Home Affairs, 2021)
The effect of rural development in reducing the poverty gap and economic growth has not been much analyzed in recent studies. This study examines the effects of rural development (as calculated by using the Village Development Index, VDI) on poverty and economic growth. Precisely, poverty is measured by the depth of poverty (as measured by Poverty Gap Index, P1) and poverty severity (as measured by Poverty Severity Index, P2) using the aggregate data at the district level in Indonesia. Understandably, many factors influence the effort to reduce the poverty gap in rural areas, and it can be started by improving rural economic development. The result of this study indicates that regions with the VDI categorized as â€œindependentâ€ and â€œdevelopedâ€ villages have the potential to reduce the depth of poverty and poverty severity in its areas and to increase economic growth. In contrast, underdeveloped and very underdeveloped regions in their VDI category experienced a more significant gap in the depth and severity of the poverty. This result implies that the Indonesian government must accelerate and improve the development of rural areas, especially in less developed regions. Thus, a better rural development status will attract more opportunities to grow rural economic activities and improve the community welfare.